THE CORRELATION OF THE APOE GENE IN PATIENTS WITH PROGRESSIVE MEMORY LOSS AFTER COVID-19 CONTAMINATION - Pedro do Valle Varela, João; Ferraço Perim, Andrezza; de Figueiredo Moutinho, Bruno; Chebabe de Azevedo, Giselle; Machado Pinto Nader, Jacquelline; Merçon Leal Reis, Beatriz; Ferro Firme Pina, Eduarda; Spinassé Del Caro, Elisa; Abreu Almeida, Breno; Luiz Teixeira Fully, Fabio (Health and Society, 2024)
Progressive memory loss is one of the neurological sequelae reported in patients who have recovered from COVID-19. The APOE gene, which encodes apolipoprotein E, has been associated with neurodegenerative disorders and may play a role in the vulnerability of certain individuals to brain damage caused by coronavirus infection. Understanding this correlation can provide important insights for the treatment and follow-up of post-COVID-19 patients. The objectives of this study are to investigate the association between the APOE gene and progressive memory loss in post-COVID-19 patients, to assess whether the presence of certain APOE gene variants is related to a higher risk of developing progressive memory loss after infection, and to identify possible mechanisms by which the APOE gene may influence vulnerability to memory loss in patients with a history of COVID-19. The methodology in question is a bibliographic review, with a narrative and exploratory method, using the PubMed, Scopus, Web of Science and Google Scholar databases, using the health sciences descriptors “ApoE Gene and Covid-19”, “Covid-19 and Genetics”, “Covid-19 and Alzheimer’s Disease” and “Covid-19 and Memory Loss”, generating a total of 78 articles, 11 of which were selected for this study. In addition, guiding questions were outlined, as well as the use of inclusion and exclusion criteria for better performance. Studies have suggested that carriers of the APOE4 genetic variant have a higher risk of developing neurodegenerative diseases, such as Alzheimer’s disease. This variant may also be associated with an increased risk of brain damage in COVID-19 patients. The presence of the APOE4 gene may influence the inflammatory response and neuronal regeneration after infection, contributing to progressive memory loss. In addition, the severity of the COVID-19 infection and the presence of neurological complications during the disease may affect the risk of developing progressive memory loss in post-COVID-19 patients. Factors such as age, comorbidities and immune response may also play a role in this correlation. The correlation between the APOE gene and progressive memory loss in post-COVID-19 patients highlights the importance of genetic and clinical studies to identify individuals at greater risk of developing neurological sequelae after infection. Understanding the mechanisms underlying this correlation could lead to the development of more effective prevention and treatment strategies for these patients.